Imóveis protegidos legalmente, mas não concretamente: Reflexões visando uma prática preservacionista mais efetiva para Ribeirão Preto-SP - Vilas Boas, Flávia Fernanda Segismundo (2019)
The research aims to establish reflections on the preservation and conservation of heritage assets that have had their value recognized, being legally protected by the law of tipping, but are in a state of abandonment, losing the memory of the city. We seek to problematize the difficulties of applying preservation policies, as well as the formulation and implementation of safeguard instruments, and the relations and clashes between the agents involved in this context, adopting as object of study some real estate listed in the city of Ribeirão Preto. - SP. From the analysis of the performance of the preservation organs, privileging the municipal scale, and the relation of memory and belonging established - or not - between the population and the architectural goods, we seek, first, to understand the general panorama in which they are inserted. and how the patrimonial processes occur in the municipality. The city chosen as a territorial clipping is the municipality of Ribeirão Preto, interior of the state of São Paulo. The problem raised came from a previous survey, carried out in 2016, where, when surveying a set of assets of heritage interest in the city, there was the abandonment of several copies important to its history, even though many were already overturned, but awaiting solutions of legal proceedings between the public and the private. It is noteworthy that this is a common scenario where this situation is repeated in many cities - small, medium or large - not only in the state of São Paulo, but as this is a problem that occurs nationwide. The body responsible for the protection of the cultural assets of the city of Ribeirão Preto - SP is the CONPPAC / RP (Council for the Defense of the Historical and Cultural Heritage of the city of Ribeirão Preto) and according to the information collected, the abandonment rates of the goods of interest. up to 40%. In view of this scenario, once the abandonment of many assets that have already been legitimized has been verified, it is intended to verify the real effectiveness of the protection and safeguard mechanisms, their scope and limitations in the effective preservation of heritage, focusing on policies and adopted instruments and their applications, using some selected properties to illustrate such reality. The general analysis and the specific cases aim to point out the main impasses to be resolved, so as to establish reflections and perspectives on the articulation between the existing instruments and the agents involved, a better relationship between them, seeking a better efficacy within the framework. municipal heritage management.